Simultaneous Quantification of Methotrexate and Its Metabolite 7-Hydroxy-Methotrexate in Human Plasma for Therapeutic Drug Monitoring - Xinxin Ren; Zhipeng Wang; Yunlei Yun; Guangyi Meng; Xialan Zhang; Huamin Ding; Ying Xu; Hansheng Bai; Jing Liu; Xia Li; Shouhong Gao; Lifeng Huang; et al. (International Journal of Analytical Chemistry)
Objective. To establish and validate a simple, sensitive, and rapid liquid chromatography tandem mass spectrometry (LC-MS/MS) method for the determination of methotrexate (MTX) and its major metabolite 7-hydroxy-methotrexate (7-OH-MTX) in human plasma. Method. The chromatographic separation was achieved on a Zorbax C18 column (3.5 μm, 2.1 × 100 mm) using a gradient elution with methanol (phase B) and 0.2% formic acid aqueous solution (phase A). The flow rate was 0.3 mL/min with analytical time of 3.5 min. Mass spectrometry detection was performed in a triple-quadruple tandem mass spectrometer under positive ion mode with the following mass transitions: m/z 455.1/308.1 for MTX, 471.0/324.1 for 7-OH-MTX, and 458.2/311.1 for internal standard. The pretreatment procedure was optimized with dilution after one-step protein precipitation. Results. The calibration range of methotrexate and 7-OH-MTX was 5.0-10000.0 ng/mL. The intraday and interday precision and accuracy were less than 15% and within ±15% for both analytes. The recovery for MTX and 7-OH-MTX was more than 90% and the matrix effect ranged from 97.90% to 117.60%. Conclusion. The method was successfully developed and applied to the routine therapeutic drug monitoring of MTX and 7-OH-MTX in human plasma.